The efficacy of intravenous artesunate in treatment of severe malaria - Tadzimirwa, Ratidzo (My University, 2018)
BACKGROUND In South Africa (SA), malaria is endemic in three provinces, Mpumalanga, KwaZulu-Natal and Limpopo and resulted in 87 deaths during 2011. The Artesunate versus quinine in the treatment of severe falciparum malaria in African children (AQUAMAT) trial showed superiority of intravenous (IV) Artesunate compared to quinine, however its use in the intensive care (ICU) is not widely studied. METHODS We performed a retrospective review of artesunate treated malaria patients admitted to the 2 academic ICUS’s (April 2010 to 2014). RESULTS A total of fifty-six patients were included. The mean age of patients was 40.3 years, standard deviation (SD) 11.6. There were 40 male patients (71.4%). The mean Apache II score was 19 (SD 5.4) with a predicted mortality of 32.2%. A total of 48% of patients had at least one co-morbidity with human immune deficiency virus (HIV) being the most prevalent (32%). 71.4% travelled to a malaria area, 26.8% had no travel history and 1.8% unknown travel. We observed a lower than predicted mortality rate of 21.4%, standardised mortality ratio of 0.67. Heart rate, respiratory rate and Glasgow Coma Scale (GCS) all improved significantly from admission to discharge, (p≤0.01). Markers of severe malaria: acidemia, bilirubin, urea and bleeding risk (platelets) also improved, (p≤0.01). Non-survivors had a lower GCS and worse acidemia on Day one, (p≤0.01). Mechanical ventilation was associated with an increased risk of death, Odds ratio (OR) 35, 95% confidence interval (CI) 7.0- 182, as was vasopressor use, OR 4.3, CI 1.7-11.4. CONCLUSION IV Artesunate was found to be efficacious and associated with a lower than predicted mortality in patients with severe malaria requiring ICU admission.
A research report submitted to the University of the Witwatersrand, Johannesburg in fulfillment for the requirements of the degree of Master of Medicine 2018